The Red Danube The big picture - Sidney, George 1916-2002; Wilson, Carey 1889-1962; Kaus, Gina 1893-1985; Wimperis, Arthur 1874-1953 (Warner Home Video, 2012)
This is one of the Red-baiting genre designed to demonstrate Hollywood's political credentials at the height of the Cold War. The representation of life in postwar Vienna sought to expose the duplicity of the Russians in repatriating displaced Soviet subjects specifically here a ballerina on the run from Russian agents. The lampooning of the occupying Allied administration in Vienna, criticised at the time of the film's release, now seems not entirely misplaced in the light of what has subsequently emerged about such repatriations. The effectiveness of the central drama is generally aided by the casting but hampered by a routine romantic sub-plot and wordy exchanges about God and organised religion between an agnostic British Army Colonel and a Mother Superior